Efficacy and outcomes of continuous peritoneal dialysis versus daily intermittent hemodialysis in pediatric acute kidney injury - Basu, Biswanath; Mahapatra, Tapan Kumar Sinha; Roy, Birendranath; Schaefer, Franz (Pediatric nephrology, 2016)
Acute kidney injury (AKI) requiring renal replacement therapy (RRT) is associated with high patient morbidity and mortality. There is no consensus on the best RRT modality for pediatric AKI.